HKS Misinfo Review 2021
DOI: 10.37016/mr-2020-83
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy is associated with more discerning accuracy judgments but not sharing intentions

Abstract: It has been widely argued that social media users with low digital literacy—who lack fluency with basic technological concepts related to the internet—are more likely to fall for online misinformation, but surprisingly little research has examined this association empirically. In a large survey experiment involving true and false news posts about politics and COVID-19, we found that digital literacy is indeed an important predictor of the ability to tell truth from falsehood when judging headline accuracy. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…It is important to bear in mind the difference between sharing and accuracy judgments, which have been shown to be largely distinct Sirlin et al, 2021). Our findings challenge a dual-process interpretation of the accuracy prompt effect on news sharing.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…It is important to bear in mind the difference between sharing and accuracy judgments, which have been shown to be largely distinct Sirlin et al, 2021). Our findings challenge a dual-process interpretation of the accuracy prompt effect on news sharing.…”
Section: Discussionsupporting
confidence: 43%
“…"; Thomson & Oppenheimer, 2016) that cue an incorrect intuitive response (first place), but people who spend more time deliberating are more likely to answer correctly (second place) (Travers et al, 2016). Notably, people who perform better on the CRT can not only better discern true from false news (Bago et al, 2020;Pennycook & Rand, 2019;Ross et al, 2021), but may also share higher-quality news (Mosleh et al, 2021;Pennycook et al, 2020;but see Osmundsen et al, 2021;Sirlin et al, 2021).…”
mentioning
confidence: 99%
“…Previous research has shown that adult education and digital literacy training can help adults learn to navigate problematic information (Seo et al, 2020;Sirlin et al, 2021). Problematic information is an umbrella term that includes information that is "inaccurate, misleading, inappropriately attributed, or all together fabricated" (Jack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As other librarians have noted, "The tactics we've taught students for evaluating items one at a time provide slim defenses against the networked efforts of organizations that flood feeds, timelines, and search results." 3 In fact, as has been recently confirmed in a study conducted on digital literacy, 4 the ability to correctly evaluate information does not predict whether an individual will choose to spread misinformation. While this study named the literacy at hand as "digital," the competencies involved clearly have overlap with what librarians consider to be information literacy and with the content of so many of our one-shots.…”
mentioning
confidence: 98%